Analysis of Interleukin-17 Levels in Patients with Thrombocytopenia - Lidwina Septie Christyawardani; Mansyur Arief; Uleng Bahrun (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Thrombocytopenia or platelet deficiency is a condition, in which platelet level in the blood circulation is below normal, which is less than 150,000 cells/µl. Thrombocytopenia is classified into some conditions, including decreased platelet production, increased need for platelets, and other thrombocytopenia. The need for increased platelets can be subdivided into primary immune thrombocytopenia, secondary immune thrombocytopenia, non-primary ITP, and thrombocytopenia that are not immune-mediated. Several cytokines play a role in the process of thrombocytopenia, one of which is Interleukin-17 (IL-17) that will be further discussed in this study. A previous study reported that IL-17 production increased in ITP and cITP patients. The objective of this study was to analyze the IL-17 levels and figure out the differences in IL-17 levels in the serums of patients with primary ITP and secondary ITP. The samples were taken from Wahidin Sudirohusodo Hospital and the specimens were examined in the Research Unit Laboratory of the Faculty of Medicine, Universitas Hasanuddin/Hospital of Universitas Hasanuddin. The comparative test resulted in p-value = 0.005, where p <α = 0.05; and therefore, there was a significant difference between IL 17 levels in ITP and non-primary ITP.